MODELING OF GEOCHEMICAL REACTION OF MINE ACID WATER DETERMINATION USING LABORATORY SCALE OPEN FLY ASH CHANNEL - SALMAN SAID (NIM : 22115007), MOHAMMAD
Acid Rock Drainage (ARD) is an important environmental impact from mining activities, both ore and coal mines which are oxidized with sulfide minerals. This issue becomes increasingly important if the ARD handling is not carried out properly, it will become a burden in the post-mining period. Materials used in acid mine water treatment are materials that have alkalinity such as limestone but fly ash or coal residual ash has alkalinity levels and so far is only considered as B3 waste because it can be contaminant contaminants, therefore research is conducted to examine more in regarding the use of fly ash as a neutralizing material. In this study fly ash is used as the main ingredient of neutralizer by using open fly ash channel, this study aims to determine the effectiveness of the use of fly ash in the acid mine water neutralization process and to determine the factors that affect the level of efficiency and effectiveness of open fly ash scale channel laboratory. This experiment uses a PVC pipe with a length of 100 cm and a diameter of 5.08 cm with a sample weight of 600 grams (30 cm on the channel). The research simulation was conducted with 2 scenarios with acid mine water content as independent variables (Channel 1: Water + H2SO4, Channel 2: Water + H2SO4 + Fe (200ppm)) with sampling per500 ml at the outlet channel. Simulation time on channel I lasts 67 days with a number of samples 31, in channel II the simulation lasts for 46 days with the number of samples 13. Efficient level of neutralization of channel I pH 124.6% while channel II 81.87% with a target pH 7. Sample leachate channel I shows a decrease in pH (9.84-3.05) and channel II leachate sample shows a decrease in pH from pH (9.38-2.87). The results of this study indicate that the level of efficiency and age of the channel on channel I is higher than channel II. Elemental test results (XRF) on fly ash used in this test showed an increase in the content of Ca and Fe. Characteristics of acid mine drainage become one of the factors that influence the efficiency of open fly ash channel. Iron and gypsum precipitation affects channel efficiency because it causes porosity and permeability of the channel to decrease and cover the surface layer on the fly ash so that the neutralization process becomes ineffective.